Increased blood pressure variability during the subacute phase in patients with ischemic stroke presenting with a low ankle‐brachial index. Issue 5 (5th March 2020) - Naito, Hiroyuki; Hosomi, Naohisa; Kuzume, Daisuke; Nezu, Tomohisa; Aoki, Shiro; Morimoto, Yuko; Kinboshi, Masato; Yoshida, Takeshi; Shiga, Yuji; Kinoshita, Naoto; Ueno, Hiroki; Noma, Kensuke; et al.
Abstract : Aim: This study aimed to evaluate the associations of blood pressure (BP) variability in patients with ischemic stroke during the subacute phase using ambulatory blood pressure monitoring and the ankle‐brachial index (ABI). Methods: We retrospectively examined 831 consecutive patients (women 44.8%, mean age 76 ± 12 years) with acute ischemic stroke who underwent 24‐h ambulatory blood pressure monitoring during the subacute phase of stroke (median 9 days from onset) and an ABI examination. BP variability was evaluated by assessing the standard deviation and coefficient of variation of systolic BP and diastolic BP. A low ABI was defined as an ABI <0.9. Results: Of the 831 patients, 201 (24.2%) had a low ABI. Older age, lower body mass index, diabetes mellitus, chronic kidney disease, atrial fibrillation and a higher National Institutes of Health Stroke Scale score at admission were independently associated with a low ABI. The patients with a low ABI had a higher mean 24‐h diastolic BP, higher standard deviation of both BP measurements (systolic BP and diastolic BP) and a higher coefficient of variation in both BP measurements than those with a higher ABI. According to the multivariable linear regression analysis, a low ABI was independently associated with increased BP variability (a high standard deviation or coefficient of variation of both BP measurements) after adjusting for baseline confounders. Conclusions: A low ABI was associated with increased BP variability during the subacute ischemic phase. Geriatr Gerontol Int 2020; 20: 448–454 .